2004
DOI: 10.1145/971617.971622
|View full text |Cite
|
Sign up to set email alerts
|

The role of personality in Web-based distance education courses

Abstract: Before investing in a Web-based education program, managers should consider how effective it will be when paired with employee personality traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 8 publications
2
24
1
2
Order By: Relevance
“…Open-minded students reported a higher DLW. This finding is consistent with the literature: Santo (2001) found that students with higher scores on openness to experience also express positive opinions of DL and they learn effectively when taking DL (Kim & Schniederjans, 2004).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Open-minded students reported a higher DLW. This finding is consistent with the literature: Santo (2001) found that students with higher scores on openness to experience also express positive opinions of DL and they learn effectively when taking DL (Kim & Schniederjans, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…have strong implications on learning style, and BIG-5 represents the dominant conceptualization of personality in the current literature (Kim, 2011;Kim &Schniederjans, 2004). Research on personality and chronotype indicated that eveningness is related to extraversion, impulsivity, novelty seeking, depressive symptomatology as well as openness and, to smaller extent, psychoticism (psychopathology) while morningness is related to conscientiousness, agreeableness, persistence, and emotional stability (see Adan et al, 2012;Tsaousis, 2010).…”
Section: Briggs (Mbti) and The Big Five Personality Model (Big-5) Mbmentioning
confidence: 99%
“…Although results have been mixed, but generally support a significant relationship between personality and performance. Kim and Schniederjans (2004) found a significant relationship between performance and each of the Big Five dimensions except extroversion; Lee and Lee (2006) found a relationship between personality and interaction in web-based threaded discussion; and Butler and Pinto-Zipp (2006) found several significant relationships which were consistent with personality traits. Pavalache-Ilie and Cocorada (2014) investigated the relations between some of the student's personality characteristics and some dimensions of online learning (preferred learning methods, student's needs, relations with the teacher and classmates).…”
Section: Introductionmentioning
confidence: 97%
“…Many educational psychologists have claimed that personality influences the way learners actively involution in their learning processes as well as whether they take responsibility for self-direction and discipline (Kim, Lee, & Ryu, 2013). The relationship between personality and academic performance has been examined in the context of distance and online education (Butler & Pinto-Zipp, 2006;Irani, Telg, Scherler, & Harrington, 2003;Kanuka & Nocente, 2003;Kim & Schniederjans, 2004;Lee & Lee, 2006). Although results have been mixed, but generally support a significant relationship between personality and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Many universities are now beginning to develop and deliver their programs through MMLSs. At the same time, studies done on MMLSs have mainly focused on determining how to use internet-based tools/objects to support instruction, to assess user satisfaction (Wang, 2003), and to characterize the internet-based learning student (Kim & Schniederjans, 2004;Lu, Yu, & Liu, 2003). Some studies have only recently examined the development and design of learning objects and their effectiveness in demonstrating that learning did occur (Krauss & Ally, 2005;Salas & Ellis, 2006).…”
Section: Introductionmentioning
confidence: 99%